Religious monuments as a new type of object: genealogy and actuality of a form of catholic presence in public spaces - Giumbelli, Emerson Alessandro (GIS - Gesture, Image and Sound - Anthropology Journal, 2020)
Based on an ethnographic scenario involving the recent construction of a statue of large proportions representing a catholic saint, this paper attempts to answer the following question: What constitutes a monument? This study articulates inspirations to guide the anthropology of objects with references that build a material approach of religion. The original role of Christ the Redeemer is taken into account as a prototype for a new kind of religious object. The presence of such objects denoting realist and colossal representations of religious figures is persistent given the crisis affecting monumental paradigms until the beginning of the twentieth century. The results imply these recent religious monuments of the sort function less as a memorial and more as a means to establish certain forms of catholic presence in public space.